ADAPTIVE PRINCIPAL LEADERSHIP FOR DEVELOPING TEACHERS' DIGITAL COMPETENCE IN RESOURCE-CONSTRAINED SCHOOLS - Ridha Amalia; Gita Lestari; Silpa Edowai; Yeremias Rahanra; Deby Siska Bogar; Rivaldo Paul Telussa (CV. TOTUS TUUS, 2027)
This study examines how principal leadership supports the development of teachers' digital competence in a resource-constrained faith-based junior high school in Nabire, Papua. A descriptive qualitative case-study design was used to investigate the leadership process within one school. The principal served as the primary participant, while teacher informants provided supporting perspectives. Data were generated through semi-structured interviews and direct school-based observations and analyzed through data condensation, data display, and conclusion drawing and verification. The findings identify six interrelated practices: role modelling and motivation, participatory digital-program planning, annual training and peer mentoring, technology-focused supervision, incremental resource mobilization, and adaptive responses to internet and device constraints. Participant accounts and observations indicated increased use of presentations and instructional videos and greater student engagement during some technology-supported lessons. The study did not directly measure achievement gains or establish causal effects. The case suggests that digital leadership in resource-constrained schools operates as an adaptive support cycle combining professional learning, distributed peer expertise, supervision, and infrastructure improvisation. The findings are transferable primarily to schools with comparable organizational and infrastructural conditions.